Sodium butyrate inhibits colitis-associated colorectal cancer through preventing the gut microbiota dysbiosis and reducing the expression of NLRP3 and IL-1β. (December 2021) - Liu, Huahuan; Bian, Zhongbo; Zhang, Qiuyu; Xiao, Zhipeng; Cao, Yu; Sun, Xiaodie; Qin, Yong; Mao, Lianzhi; Chu, Xinwei; Liao, Wenzhen; Zha, Longying; Sun, Suxia
Graphical abstract: Highlights: Sodium butyrate (NaB) ameliorated colitis and colitis associated cancer induced by AOM/DSS in mice. NaB attenuated colon inflammation induced by AOM/DSS through inhibiting NLRP3 inflammasome. NaB protected mice from AOM/DSS-induced CAC by improving colon inflammation and regulating gut microbiota dysbiosis. Abstract: Sodium butyrate (NaB) is a by-product of dietary fiber that has an anti-tumor effect on colorectal cancer (CRC). The aim of this study was to explore the effect of NaB on tumor and colitis using a colitis-associated colorectal cancer (CAC) model. CAC model was induced in mice by administration of azoxymethane (AOM) and dextran sulfate sodium salt (DSS). 0.1 M NaB in drinking water, or intraperitoneal injection of NaB (1 g/kg body weight) was given during the study period. NLRP3 inflammasome-related molecules were detected. The composition and taxonomy of colorectal microbiota were analyzed. NaB increased spleen index decreased by AOM/DSS. NaB attenuated tumors by reducing tumor load and tumor size in AOM/DSS-induced mice. NaB protected mice from CAC by improving colitis and inhibiting expression of NLRP3 and IL-1β. NaB regulated gut microbiota dysbiosis induced by AOM/DSS. In conclusion, NaB inhibited CAC by ameliorating the gut microbiota dysbiosis and inhibiting colitis.